Laser surgery versus radiotherapy for T1a glottic carcinoma: a meta-analysis of oncologic outcomes. (2nd November 2017) - Huang, Guanjiang; Luo, Mengsi; Zhang, Jingxuan; Liu, Hongbing
Abstract: Objectives: A meta-analysis was conducted to compare oncologic outcomes for patients of T1a glottic carcinoma who were treated with laser surgery (LS) or radiotherapy (RT). Methods: All related studies published up to October 2016 were acquired by searching PubMed, EMBASE, and Cochrane were conducted by two authors, with the index words: vocal, glottis, larynx, laser, surgery, cordectomy, radiotherapy, radiation, irradiation, carcinoma, and cancer. Relative studies which compared oncologic outcomes between LS and RT were included. Results: A total of nine eligible studies were included for the analysis, which contained two prospective studies and seven retrospective studies. LS has increased larynx preservation (OR = 3.86, 95% CI = 1.47–10.13, p  = .006) compared with RT group. No statistical difference was observed between LS group and RT group in terms of local control, overall survival, and disease-specific survival. There was a slight trend in terms of local control, overall survival, and disease-specific survival that all favored LS, although all data did not reach the level of statistical significance. Conclusions: The results of this meta-analysis indicate that LS may be a better option for the treatment of T1a glottic carcinoma because patients underwent LS may benefit from increased larynx preservation compared with RT. However, more multi-center randomized controlled trials would be urgently needed to prove these differences.